Osteoid osteoma mimicking overuse syndromes in athletes - Giombini, A.; Dragoni, S.; Averna, T.; Ripani, M.; Longo, U. G.; Maffulli, N. (The Journal of Sports Medicine and Physical Fitness, 2009)
This article reports the clinical features, findings at imaging, management and outcome of five athletes who presented with osteoid osteoma. The diagnosis was missed initially in all the athletes, who were managed for an overuse syndrome for many months before receiving a correct diagnosis. Osteoid osteoma can cause atypical pain, and therefore lead to delay in diagnosis and inappropriate management. Each injured athlete must be fully evaluated by history, physical examination and appropriate imaging investigations to minimize the rate of misdiagnosis and underestimation, unnecessary procedures, and delayed management.